Effect of incoming and outgoing exchangeable anions on the release kinetics of phenoxyherbicides nanohybrids - Sarijo, Siti Halimah; Hussein, Mohd. Zobir; Yahya, Asmah; Zainal, Zulkarnain (Elsevier, 2010)
The release of chlorophenoxyherbicides agrochemicals, namely 2-chloro- (2CPA), 4-chloro and 2,4,5-trichloro (TCPA) phenoxyacetates from their nanohybrids into various aqueous solutions; carbonate, sulfate and chloride was found to be controlled by pseudo-second order rate expression. The percentage saturated released was found to be anionic-dependent, in the order of carbonate > sulfate > chloride for the release media and 2CPA > 4CPA > TCPA for the anionic guests. This study demonstrates that the release of the phenoxyherbicides agrochemicals from the nanohybrid compounds can be tuned by choosing the right combination of exchangeable anions both the incoming and the outgoing anions.